Depression, anxiety and self‐care behaviours of young adults with Type 2 diabetes: results from the International Diabetes Management and Impact for Long‐term Empowerment and Success (MILES) Study. Issue 1 (12th September 2014) - Browne, J. L.; Nefs, G.; Pouwer, F.; Speight, J.
Abstract Aim Young adults with Type 2 diabetes have higher physical morbidity and mortality than other diabetes sub‐groups, but differences in psychosocial outcomes have not yet been investigated. We sought to compare depression and anxiety symptoms and self‐care behaviours of young adults with Type 2 diabetes with two matched control groups. Methods Using cross‐sectional survey data from the Australian and Dutch Diabetes Management and Impact for Long‐term Empowerment and Success (MILES) studies, we matched 93 young adults (aged 18–39 years) with Type 2 diabetes (case group) with: (i) 93 older adults ( ≥ 40 years) with Type 2 diabetes (Type 2 diabetes control group; matched on country, gender, education, diabetes duration and insulin use) and (ii) 93 young adults with Type 1 diabetes (Type 1 diabetes control group; matched on country, gender, age and education). Groups were compared with regard to depression symptoms (nine‐item Patient Health Questionnaire), anxiety symptoms (seven‐item Generalised Anxiety Disorder questionnaire) and frequency of selected self‐care behaviours (single item per behaviour). Results Participants in the case group had higher depression scores (Cohen's d = 0.40) and were more likely to have clinically meaningful depressive symptoms (Cramer's V = 0.23) than those in the Type 2 diabetes control group. Participants in the case group had statistically equivalent depression scores to the Type 1 diabetes control group. The groups did not differ in anxiety scores. Those in the case group were less likely than both control groups to take insulin as recommended (Cramer's V = 0.24–0.34), but there were no significant differences between the groups in oral medication‐taking. The case group were less likely than the Type 2 diabetes control group to eat healthily (Cramer's V = 0.16), and less likely than the Type 1 diabetes control group to be physically active (Cramer's V = 0.15). Conclusions Our results suggest that Type 2 diabetes is as challenging as Type 1 diabetes for young adults and more so than for older adults. Young adults with Type 2 diabetes may require more intensive psychological and self‐care support than their older counterparts.